Expenditure and Financial Burden for Stomach Cancer Diagnosis and Treatment in China: A Multicenter Study - Zhang, Kai; Yin, Jian; Huang, Huiyao; Wang, Le; Guo, Lanwei; Shi, Jufang; Dai, Min (Frontiers in Public Health, 2020)
Background: Stomach cancer is a huge threat to the health of Chinese people. However, few studies have looked into the expenditure and financial burden due to stomach cancer in China. Methods: To estimate the direct (medical and non-medical) and indirect expenditure for diagnosis and treatment for stomach cancer patients in China, a multicenter survey was conducted in 37 tertiary hospitals in 13 provinces across China from 2012 to 2014. Each enrolled patient was interviewed through a structured questionnaire. The medical and non-medical expenditure at different clinical stages, the composition of non-medical expenditure, and the time loss for the cancer patient and their family were assessed. All expenditure data were inflated to the 2014 Chinese Yuan [CNY; 1 CNY = 0.163 USA dollar (USD)]. Results: A total of 2,401 stomach cancer patients with a mean age of 58.1 ± 11.4 years were included, predominately male. The overall average direct expenditure per patient was estimated to be US $9,899 (medical expenditure 91.2%, non-medical expenditure 8.8%), and the expenditures for stage I, II, III, and IV were $8,648, $9,004, $9,810, and $10,816, respectively; expenditure in stage III and IV was significantly higher than that in stages I and II (p < 0.05). One-year out-of-pocket expenditure of a newly diagnosed patient with stomach cancer was $5,368, accounting for 63.8% of their previous-year household income, which led to 79.2% families suffering an unmanageable financial burden. The average loss of time for patients and caregivers was $996. Conclusions: This study indicated that the economic burden of stomach cancer in urban China was onerous. Effective intervention is necessary to reduce the financial burden by reducing the personal payment ratio and increasing the reimbursement ratio.